The conducting pheromone monitoring of the main pests of the orchard - Borzykh, A.; Tkalenko, G.; Kirichuk, I.; Chelombitko , A. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2020)
Goal. Analysis of the latest methods for identifying pests of an orchard using pheromone monitoring and factors affecting its implementation.Methods. The studies were carried out in accordance with modern methodological approaches to pheromone monitoring of pests of fruit plantations.Results. The principles of pheromone monitoring in an orchard are given to identify harmful and quarantine organisms, which makes it possible to obtain information about the presence of pests in a certain area, determine their number, development dynamics, and, on the basis of the data obtained, plan and carry out appropriate phytosanitary measures. The main pests of the orchard of the Lepidoptera and Hemiptera classes have been identified, monitoring of which is carried out using pheromone traps. Methodological recommendations are given for conducting pheromone monitoring in fruit plantations to identify the eastern fruit moth (Grapholitha molesta Busck), Californian and mulberry scale insects (Pseudaulacaspis pentagona Targ.-Tozzetti, Quadraspidiotus perniciosus Comst), American white butterfly (Hyphantria cune). The advantages of the pheromone method over other monitoring methods are presented. The main factors that affect the catch of pests with pheromone traps are described.Conclusions. The information obtained with the help of pheromone traps is a component of effective programs — systems of integrated plant protection against pests, which combine the use of a complex of biological, chemical, agrotechnical measures, as well as fundamental for planning measures to prevent emergencies in a phytosanitary state. The informativeness and reliability of pheromone monitoring makes it possible to substantiate and develop instrumental monitoring technologies that reduce the number of chemical treatments by up to 30%, increase labor productivity by 75%, reduce costs by 70%, and increase the efficiency and reliability of accounting.